2013
DOI: 10.1016/j.theriogenology.2013.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non–sperm cells removal with single-layer colloidal centrifugation on myeloperoxidase concentration in post-thaw equine semen

Abstract: Myeloperoxidase (MPO) is a pro-oxidant enzyme contained in and released by neutrophils during degranulation or after lysis. Post-thaw semen contains MPO and its concentration is associated with decreased sperm motility. Recently, MPO concentration in post-thaw semen was shown to be associated with the presence of non-sperm cells (NSC). The objective of this study was to evaluate the effect of a single-layer colloidal centrifugation before cryopreservation on NSC and MPO concentrations in equine semen. The expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Total MPO concentrations observed in fresh semen are comparable with previously published values (Ponthier et al. , ), but very high when compared to MPO concentrations observed in other equine biological fluids (Art et al. ; Grulke et al.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Total MPO concentrations observed in fresh semen are comparable with previously published values (Ponthier et al. , ), but very high when compared to MPO concentrations observed in other equine biological fluids (Art et al. ; Grulke et al.…”
Section: Discussionsupporting
confidence: 89%
“…This report confirms that free MPO is present in stallion fresh semen as previously described . Total MPO concentrations observed in fresh semen are comparable with previously published values (Ponthier et al , 2013, but very high when compared to MPO concentrations observed in other In raw semen, spermatozoa concentration, total motility and total MPO concentration were all correlated. Recently, raw semen concentration has been directly correlated with CASA values (Parrilla-Hernandez et al 2012).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Consequently, a better understanding of sperm function in relation to clinical andrology and sperm biotechnologies [1,2] has arisen. Relevant advances in stallion sperm biology include, among others, the following: the understanding of osmotic shock [3][4][5] and its implications on cryopreservation, which promoted the development of new protocols based on more permeant cryoprotectants [6][7][8][9][10]; advances in understanding the role of reactive oxygen species (ROS) [11][12][13][14]; and the development of practical methods for stallion sperm separation and selection through colloidal centrifugation [15][16][17][18][19][20][21]. More recently, the understanding of sperm bioenergetics and mitochondrial functionality have become two hot topics in stallion andrology.…”
Section: Introductionmentioning
confidence: 99%